Q: How do you solve x3 plus 4x2 plus 6x plus 24?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

5x+3+x=24 6x+3=24 6x=21 x=3.5

It can't be factored because the discriminant is less than zero.

From what i understand the equation is like this; (3 * 2 ) + 6x + 24 = 0 6 + 6x +24 = 0 6x = - 24 - 6 6x = - 30 x = - 5

6x + 5 = 0 (I'm assuming) 6x = -5x = -5/6

Related questions

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x

5x+3+x=24 6x+3=24 6x=21 x=3.5

This is how I did it:8x3+4x2+6x+3[8x3+4x2]+[6x+3][(4x2)(2x+1)]+[(3)(2x+1)]....as you can see, this is in the general form of ab+cb, which factored is b(a+c), so:(2x+1)(4x2+3)

4x2 - 3x - 9

2(x + 1)(2x + 1)

2(4x2 + 6x - 1)

It can't be factored because the discriminant is less than zero.

Well im not a mathmatician but my guess is that 2X2-6X+24 doesn't equal anything so you cant solve for X that's my guess

4(x2 - 6x + 13)

From what i understand the equation is like this; (3 * 2 ) + 6x + 24 = 0 6 + 6x +24 = 0 6x = - 24 - 6 6x = - 30 x = - 5

16x+9 without the rest of the equation, what this equals, I can't solve